Site-specific factors influencing Hymenoscyphus fraxineus spore dispersal: the role of understorey vegetation and slope steepness in ash dieback spread - Aneliya RAYKOVA (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
Ash dieback (ADB), caused by Hymenoscyphus fraxineus, is a severe threat to Fraxinus excelsior populations across Europe, with spore dispersal playing a critical role in disease progression. While broad-scale environmental drivers of spore dispersal are well studied, site-specific factors remain underexplored. This review uniquely explores how understorey and slope steepness influence the dispersal, deposition, and development of H. fraxineus spores, along with stand management strategies reported to impact ADB disease progression. The dense understorey vegetation creates microclimatic conditions favouring spore development and retention through increased humidity, reduced airflow, and light accessibility, while also potentially modifying transmission dynamics. Slope steepness may affect spore dynamics through gravity-driven movements of infected ash rachises, and microclimatic variation associated with slope aspect. Understanding these site-specific effects can enhance disease management strategies aimed at conserving tolerant individuals and preserving the genetic basis of tolerance for future Fraxineus excelsior generations. The review also identifies knowledge gaps and highlights the need for empirical research on context-specific management strategies across diverse forest landscapes.